Understanding the thermal stability of a 3d, 4d, and 5d element doped aluminium nanocluster through BOMD simulations - Samudre, Nikhil S.; Singh, Chandrodai Pratap; Krishnamurty, Sailaja (Molecular Simulation, 2023)
Endohedrally doped atomic clusters have generated considerable interest among computational chemists on account of their tunable chemical properties that mimic a super atom. Such endohedrally doped clusters have also been experimentally realised in the more recent past. The present work explores the practical existence of 3d, 4d and 5d doped aluminium clusters, more specifically doped Al13 cluster, by evaluating systematically their structural stability through the first principle molecular dynamical simulations. Born-Oppenheimer Molecular Dynamics (BOMD) simulations have been carried out on Al12X atomic clusters where X = Ti, V, Fe, Co, Ni, Cu, Zn, Y, Mo, Ru, Rh and W are in endohedral position. The thermal stability of such endohedrally doped clusters is quantified through parameters such as delta(rms), MSD and is an element of(pro). Electronic structure calculations reveal that endohedral doping of only Rh, Cu and Zn is preferred in the Al-13 cluster. Other dopants prefer to remain on the surface positions. However, finite temperature calculations reveal that the Al12Zn cluster undergoes surface modifications from 300K leading to a distorted icosahedral structure. Al12Cu cluster in quartet spin state is the only thermally stable cluster with Cu remaining in the endohedral position and structure retaining icosahedral confirmation till 700K.
Keywords: Al-13 atomic cluster; BOMD simulations; DFT; Endohedral doping; super atom

Quasi-molecular hydrogen storage capacity of graphene quantum dots: A dispersion corrected DFT study - Khadilkar, Pranav; Samudre, Nikhil S.; Krishnamurty, Sailaja (Journal of Energy Storage, 2024)
Efficient storage of hydrogen, green fuel with the highest energy density, remains a pressing challenge. Among the several materials investigated for their potential hydrogen storage, 2D materials, like graphene, have advantages such as mechanical strength and large surface area but fail to store hydrogen reversibly. In this context, the present computational experiment demonstrates the potential of Graphene Quantum Dots (GQDs) with 24, 40 and 42 carbon atoms for their hydrogen storage capacity in quasi-molecular mode. Factors such as edge terminations, heteroatom doping, and anchoring of metal atoms are evaluated as a function of their storage capacity. The study clearly demonstrates an enhanced storage capacity of quantum dots, particularly, when a single Ti adatom is anchored on a 24 carbon atom GQD with a storage weight % of 2.24 % w/w. The storage weight % is further noted to increase as a function of the number of Ti atoms anchored on the GQD with the highest hydrogen storage weight % of 6.1 % w/w. Importantly, the adsorption of hydrogen molecule on the Ti atom is through a quasi-molecular mode and is driven by Kubas interaction. This type of interactions makes GQDs as viable storage materials at room temperature. Secondly, the work demonstrates that GQDs offer higher storage capacities of hydrogen molecules as compared to their 2D counterparts viz., graphene sheets, making them attractive candidates to be explored experimentally.
Keywords: Density functional theory; graphene quantum dots; Hydrogen storage; Kubas interaction; Quasi -molecular adsorption; Ti adatom

Variations in packing as a function of side chains in random copolymers and its impact on charge carrier mobility - Swain, Gitanjali; Kumar, Subramani; Samudre, Nikhil S. (Macromolecular Chemistry and Physics, 2024)
Homopolymers and alternating copolymers of conjugated molecules exhibit impressive performance in electronic devices. Despite the well-established procedures, the synthesis of alternating copolymers using three monomers is not as easy as random copolymers. Besides facile synthesis, the random copolymers can match the performance of alternating copolymers in electronic devices. Herein, random copolymers are designed and synthesized comprising thienoisoindigo (TIIG), diketopyrrolopyrrole (DPP), and thiophene. The DPP monomers installed with various side chains including branched alkyl chain, branched alkyl chain with ester functionality, linear oligo ethylene glycol, and siloxane terminated alkyl chain are incorporated into the polymers (P1, P2, P3, and P4, respectively). All the thermally stable, low bandgap random copolymers exhibited strong H-type aggregation in thin film. The relationship between thin film microstructure originating from diverse side chains and the charge transport in organic field effect transistors (OFETs) is investigated. All the random copolymers exhibited predominantly p-type charge transport and a maximum hole mobility of 2 x 10-2 cm2 V-1s-1 is observed for P3. The packing of all the polymers is examined theoretically by density functional theory (DFT) and compared with experimental values obtained from grazing incident X-ray diffraction (GIXRD). Various side chains (hydrophilic and hydrophobic) affect molecular packing of random polymers which ultimately affects its thin film morphology and semiconducting performances. Linear chains provide better interchain packing by pi-pi stacking compared to bulky branched side chains. The incorporation of heteroatoms and polar groups into the side chain further enhances the interchain interactions. image
Keywords: diketopyrrolopyrrole; organic field effect transistor; random polymer; side chain engineering; thienoisoindigo

Evaluating the catalytic potential of Lithium-decorated graphene quantum dots for small molecule activation - Samudre, Nikhil S.; Tiwari, Rukminesh (Chemical Physics, 2025)
The search for effective catalysts in small molecule activation has intensified as industries seek efficient and costeffective solutions. Lithium (Li), known for its unique electronic properties, is of significant interest as a catalyst. However, its specific catalytic potential when anchored on graphene quantum dots (GQDs) has not been fully explored. This study investigates the catalytic potential of lithium (Li) adatoms on GQDs with various edge conformations (zigzag and armchair) and sizes (24 and 42 atoms). Using density functional theory (DFT), we examine the interactions of Li-decorated GQDs with small molecules such as H2, N2, CO, O2, and CO2. Our findings reveal that Li-GQD complexes exhibit optimal catalytic activity for all these molecules, based on binding energy, charge distribution, and bond length changes. The smallest GQD, coronene (24 carbon atoms), shows the most promising catalytic activity, providing experimental leads for synthesizing and testing efficient Li-anchored catalysts.
Keywords: Catalytic activity; Density functional theory; graphene quantum dots; Lithium adatom; small molecule activation

Graphitic carbon nitride supported boron quantum dots: a transition metal free alternative for di-nitrogen to ammonia reaction - Samudre, Nikhil S.; Krishnamurty, Sailaja (CHEMPHYSCHEM, 2025)
Presently, a sustainable electrochemical Nitrogen Reduction Reaction (NRR) has been essentially found to be viable on transition metal-based catalysts. However, being cost-effective and non-corrosive, metal-free catalysts present an ideal solution for a sustainable world. Herein, through a DFT-based study, we demonstrate metal-free NRR catalysts, boron quantum dots with 13 atoms as a case study and their chemically modified counterparts when anchored on graphitic carbon nitride (g-C3N4) surface. The best catalyst among the studied, a silicon-doped boron quantum dot with a cagelike structure, is found to favour the dinitrogen to ammonia reaction pathway with a low liming potential and potential rate-determining step (PDS) of -0.11 V and 0.27 eV, respectively. The present work demonstrates as to how boron quantum dots, which are reported to be experimentally synthesised, can be exploited for ammonia synthesis when supported on the surface. These catalysts effectively suppress the HER, thus establishing its suitability as an ideal catalyst. The work also represents a futuristic pathway towards a metal-free catalyst for NRR.
Keywords: Boron quantum dot; Electro-catalyst; Graphitic carbon nitride; hydrogen evolution reaction; Limiting potential; metal free catalyst; Nitrogen Reduction Reaction

Self-supported super-hydrophilic interconnected nanospikes and particles of MoS2-Ni3S2/NF with optimum d-band center for anion exchange membrane water electrolyzer - Kumar, Yogesh; Barik, Sidharth; Samudre, Nikhil S.; Kharabe, Geeta Pandurang; Chauhan, Inderjeet; Manna, Narugopal; Bhat, Suresh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
There is an imperative need for highly efficient electrocatalysts for cost-effective hydrogen production. Herein, a self-supported, hybrid composite as a bifunctional electrocatalyst is introduced. This is achieved by in situ growth of MoS2-Ni3S2 on nickel foam (NF), designated as MoS2-Ni3S2/NF, synthesized by a facile one-step hydrothermal synthesis method. MoS2-Ni3S2/NF exhibits low overpotentials of only 187 and 146 mV for OER and HER, respectively, to achieve a current density of 10 mA cm-2 in 1 M KOH. The practical application of the designed bifunctional electrocatalyst is verified by constructing the MoS2-Ni3S2/NF || MoS2-Ni3S2/NF symmetrical membrane electrode assembly (MEA) of 4 cm2 working area for the anion exchange membrane water electrolyzer. The system shows continuous electrolysis for the monitored 48 h duration. For OER, an optimum d-band center of -1.66 eV for the heterostructure is calculated from the Density Functional Theory (DFT) studies. The factors like the unique structure of the electrocatalyst, enhanced hydrophilicity, improved electrochemically accessible number of sites (ECASs), and optimum d-band center, are expected to be the primary contributors to the system's improved performance. Thus, the present finding unveils a straightforward synthesis approach for creating a stable electrocatalyst for advancing commercial water electrolysis in the realm of renewable electrochemical energy conversion.
Keywords: AEM; d-band center; electrolyzer; HER; OER

Self-healing hydrogel electrolyte enabled by dynamic polar covalent and noncovalent interactions for high-performance rechargeable zinc-metal batteries: a leap toward sustainable energy storage - Puthiyaveetil, Priyanka Pandinhare; Kurian, Rachna Maria; Samudre, Nikhil S.; Balasubramanian, Rajalakshmi; Torris, Arun; Pockil, Fayis Kanheeram; Bhat, Suresh; Ajithkumar, T. G.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Advanced Energy Materials, 2026)
Hydrogel polymer electrolytes with superior multifunctional properties are promising alternatives to aqueous electrolytes for resolving interfacial issues in rechargeable zinc-metal batteries. In this study, an intrinsic self-healing hydrogel polymer electrolyte (PHBC-4) is synthesized, engineered through an integrated approach involving the polar covalent (B & horbar;O bond), hydrogen-bond (polyvinyl alcohol-hydroxypropyl methylcellulose interface), and coordination-type (Zn & horbar;O) interactions to enable self-healing functionality. The PHBC-4 has demonstrated high ionic conductivity (4.6 x 10-2 S cm-1), good oxidative stability (2.3 V vs Zn|Zn2+), a high cation transference number (0.89), superior tensile strength (0.32 MPa), and an impressive healing efficiency of 93% achieved just within 5 min, confirming its robust self-healing capability. In Zn||Zn symmetric cells, it effectively suppresses dendrite growth, ensuring stable cycling for over 1032 h with an areal capacity of 1.0 mAh cm-2 at a current density of 1.0 mA cm-2. When paired with a Zn-doped MnO cathode in the rechargeable homemade pouch cell, the system delivers a high specific capacity of 160 mAh g-1 at 0.10 A g-1 and cycling stability up to 493 charge-discharge cycles at 2.0 A g-1. The self-healing ability of PHBC-4 HGPE is confirmed in a homemade pouch cell via OCV and charge-discharge tests, demonstrating stable performance. The DFT studies confirm molecular-level interactions within the hydrogel heterostructure.
Keywords: dendrite inhibition; flexible rechargeable zinc metal battery; high cation transference number; self-healing hydrogel polymer electrolyte

Silico imine-based ligand engineering of CALF-20 for electrocatalytic ammonia production - Samudre, Nikhil S.; Samal, Pragnya Paramita; Krishnamurty, Sailaja (ACS Sustainable Chemistry & Engineering, 2026)
Electrocatalytic ammonia synthesis is emerging as a globally compelling, sustainable alternative to the Haber-Bosch process under ambient conditions. As a result, active-site engineering has taken center stage in the development of stable and effective electrocatalysts. In this work, we report how the introduction of an imine group in the ligand backbone of CALF-20, a Zn-based, moisture-stable MOF with high surface area, results in the formation of an N-4 macrocycle for transition-metal anchoring. PBE + D3 calculations, supported by spectroscopic, ab initio molecular dynamics, and electronic analyses, identify Fe-bound modified CALF-20 as the most stable configuration among the Mn-, Fe-, Co-, Ni-, Cu-, Ru-, Rh-, Ag-, and Au-anchored within the modified CALF-20 framework. Upon modification, the d-band center shifts from -5.08 to -4.44 eV in M-Fe-CALF-20. Adsorption studies confirm activation of both N-2 and NO2, reflected by bond elongation and red-shifted IR peaks. Mechanistic studies show that M-Fe-CALF-20 selectively facilitates NH3 formation, exhibiting PDS values of 0.69 and 0.62 eV for the NRR and NO2RR, respectively, while a competitive adsorption shows a clear preference over HER. Our study illustrates how functionalization tunes CALF-20 for dual application as an adsorbent and as an electrocatalyst for NH3 synthesis and storage.
Keywords: Adsorption; CALF-20 MOF; electrocatalysis; hydrogen evolution reaction; nitrogen oxide reductionreaction (NO2RR); nitrogen reductionreaction